The rates of communal hygiene in some regions of Karaganda and positive and negative directions of them to human body - Yeleupaeva, Sh.K.; Zhumagalieva, Zh.Zh.; Korchyn, V.I. (Publ.KarSU, 2018)
The rates of regional soil, air, water of communal hygiene according to Karaganda region are analyzed, reasons of deviation from allowed concentration in some regions and research methods of them are considered in this article. For example, percentage rates of communal hygiene in Karaganda city and regions are analyzed. Negative factors influencing on human body are researched in laboratories by means of special researches and through special order. We have taken a lot of physical-chemical rates together with sanitary-epidemiological station. The aim of work is the condition of communal hygiene in regions and some information which influence on human body are given. Except the structure of harmful substances in evaluation tendency of alteration of atmospheric air in hygienic point, influence of them to human health, knowing their concentration, defining this or that ingredients are the influence of intensity. The concentration of atmospheric polluters relates to these factors: volume of extraction, length of extraction, distance of extraction, meteorological terms (direction, speed of wind, humidity, atmospheric pressure, temperature pressure, according to solar radiation). Defining the pollution of atmospheric air through laboratory observations was conducted in regional SES according to state order. Analysis was taken from 5101 research objects and regions to research. The highness of harmful substances from permitted concentration comprises 6.3 %, it has been proved that it is lower than the analysis in 2016 (2016 — 8.1 %).
Коммунально-гигиенические показатели некоторых регионов Карагандинской области и их положительное и отрицательное влияние на организм человека
Қарағанды облысының кейбір аймақтарындағы коммуналдық гигиенаның көрсеткіштері жəне оның адам ағзасына əкелетін оң жəне теріс бағыттары
Keywords: extremely-allowed concentrations (EAC); sanitary protecting regions; implementing regional nomenclatures; anthropogenic intensive level АIL; LLC; BRIS; SESU; OStRK; physical-chemical rates; World Health Organization (WHO)